Physiological myocardial 18F-FDG uptake pattern in oncologic PET/CT: comparison with findings in cardiac sarcoidosis - Takashi Norikane; Yuka Yamamoto; Yasukage Takami; Katsuya Mitamura; Takuya Kobata; Yukito Maeda; Takahisa Noma; Yoshihiro Nishiyama (Asia Oceania Journal of Nuclear Medicine and Biology, 2024)
Objective(s): Physiological myocardial 18F-fluorodeoxyglucose (18F-FDG) uptake in oncologic positron emission tomography (PET)/computed tomography (CT) is commonly observed with multiple variations under clinical fasting conditions. The purpose of the present study was to evaluate physiological myocardial 18F-FDG uptake pattern by comparing with the results in cardiac sarcoidosis.Methods: A total of 174 examinations in 174 patients without cardiac disease and 27 examinations in 17 patients with cardiac sarcoidosis were performed. The polar map images generated from 18F-FDG PET/CT data were visually assessed as “basal-ring,” “focal,” and “focal on diffuse” patterns. Semi-quantitative analysis was also performed using the regional relative 18F-FDG uptake (% uptake).Results: On visual analysis, the “focal on diffuse” pattern was the most common in both examinations (43% and 59%, respectively). The physiological % uptake in the lateral and basal septal walls tended to be higher. Subgroup analysis showed significantly higher uptake in the mid-wall and left circumflex territory. In cardiac sarcoidosis patients, there was a significant difference only between segments 2 and 15 (p=0.04). No significant differences were observed between the base-mid-apical territory and coronary artery branch territory.Conclusion: High 18F-FDG uptake in the basal septal walls is likely to be observed as both physiological uptake in patients without cardiac disease and pathological uptake in patients with cardiac sarcoidosis.